Implementasi Manajemen Keuangan dan Manajemen Sarana dan Prasarana terhadap Mutu Pembelajaran pada Sekolah Dasar Islam Terpadu ROBBANI Singosari Kabupaten Malang - Kristin Andriani; Dharmayanti Pri Handini; Mulyono Mulyono (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to determine the implementation of financial management and infrastructure management on the quality of the learning process at Robbani Integrated Islamic Elementary School, Singosari, Malang. The background of this study is based on the importance of effective and efficient management of school resources to improve the quality of basic education as a foundation for student development. School financial management includes planning, management, supervision, and accountability of education funds, while infrastructure management focuses on the procurement, utilization, and maintenance of school facilities to support the learning process. The research method used is descriptive quantitative with a population of all teachers and education personnel at Robbani Islamic Elementary School, using data collection techniques in the form of questionnaires, documentation, and supporting interviews. Data were analyzed using descriptive statistics and hypothesis testing to examine the influence between variables. The results of the study indicate that financial management at Robbani Islamic Elementary School has been implemented based on the principles of transparency, accountability, and efficiency, reflected in the management of School Operational Assistance (BOS) funds and parent fees allocated for school operations, teacher competency improvement, and facility maintenance. In addition, school facilities and infrastructure such as classrooms, laboratories, libraries, and worship and sports facilities are already available although they still need development to better support technology-based learning. Statistical analysis revealed a significant influence of financial management and infrastructure on the quality of the learning process, as reflected in student exam results, academic and non-academic achievements, and parental satisfaction. This study recommends strengthening financial management through more careful planning and improving the quality of facilities and infrastructure to support active, innovative, creative, effective, and enjoyable learning (PAIKEM). The results of this study are expected to provide input for schools, foundations, and future researchers in developing educational policies.